The Development of Market Place Activity Models in Social Sciences Subjects - Susanti, Tika; Syahza, Almasdi; Suarman, Suarman (FKIP-Universitas Riau, 2020)
Learning model is very important in the teaching and learning process. The use of the proper model will arouse students' enthusiasm and interest in learning. However, the learning model still has weaknesses that affect students cognitive development, hence it is necessary to develop the learning model. The purpose of this research is to develop a market place activity learning model by using a 4-D model consisting of define, design, development in social science subjects at SMP IT Syahruddiniyah Kampar Kiri Hilir. The respondents were 48 students from class VIIIa and VIIId. Based on data presentation and data analysis, the development of the model carried out is valid. The results value obtained from the aspect of model development 81%, the aspect of model effectiveness 98%, and the aspects of model efficiency 90%.